Variations in healthy swallowing mechanics during various bolus conditions using computational analysis of swallowing mechanics (CASM) - Lenell, Charles (Dysphagia, 2019)
Bolus properties such as volume, consistency and density have been shown to influence swallowing through the analysis of kinematics and timing in both normal and disordered swallowing. However, inherent intra- and inter-person variability of swallowing cloud interpretation of group data. Computational analysis of swallow mechanics (CASM) is an established methodology that uses coordinate tracking to map structural movements during swallowing and yields statistically powerful analyses at both the group and individual levels. In this study, the CASM method was used to determine how different bolus properties (volume, consistency, and density) altered swallow mechanics in healthy young adults at the group and individual levels. Videofluoroscopic swallow studies (VFSS) of 10 (4 female) healthy young adults were analyzed using CASM. Five bolus types were administered in each study (3×5ml 40% w/v nectar, 3×5ml 22% w/v thin, 3×5ml 40% w/v thin, 3×10ml 22% w/v thin, and 3×20ml 22% w/v thin). Canonical variate analyses demonstrated that bolus condition did not affect swallowing mechanics at the group level, but bolus condition did affect pharyngeal swallow mechanics at the individual level. Functional swallow adaptations (e.g, hyoid movement) to bolus conditions were not uniform across participants, consistent with the nonsignificant group finding. These results suggest that individual swallowing systems of healthy young individuals vary in how they respond to bolus different conditions, highlighting the intrinsic variability of the swallow mechanism and the importance of individually tailored evaluation and treatment of swallowing. Findings warrant further investigation with different bolus conditions and aging and disordered populations.